2019
DOI: 10.1021/acs.joc.9b02896
|View full text |Cite
|
Sign up to set email alerts
|

NH4OAc-Promoted Domino Route to Hydroxyarylated Unsymmetrical Pyridines under Neat Conditions

Abstract: A new metal-, oxidant-, and solvent-free ecofriendly domino method has been established for modular synthesis of a diverse range of medicinally promising hydroxyarylated unsymmetrical pyridines in good to high chemical yields with an excellent regioselectivity. This domino process involves a range of N-sulfonyl ketimines as C,N-binucleophiles, enolizable ketones, and aromatic/heteroaromatic aldehydes using ammonium acetate as an ideal promoter under neat conditions, which creates two new C–C bonds and one C–N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…On the basis of previous literature reports, ,, two possible reaction pathways are proposed as shown in Scheme . In path a , Knoevenagel condensation of diaryl ethanone 3 and aldehyde 2 leads to the formation of chalcone A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of previous literature reports, ,, two possible reaction pathways are proposed as shown in Scheme . In path a , Knoevenagel condensation of diaryl ethanone 3 and aldehyde 2 leads to the formation of chalcone A .…”
Section: Resultsmentioning
confidence: 99%
“…10 Very recently, Samanta et al reported the synthesis of unsymmetrical pyridines from N-sulfonyl ketimines, aromatic aldehydes, and ammonium acetate under neat conditions. 11 Consequently, it is still desirable to explore new, efficient methods for the construction of unsymmetrically multisubstituted pyridines.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation